Efficient and Heritable Gene Targeting in Tilapia by CRISPR/Cas9. Issue 2 (1st June 2014) - Li, Minghui; Yang, Huihui; Zhao, Jiue; Fang, Lingling; Shi, Hongjuan; Li, Mengru; Sun, Yunlv; Zhang, Xianbo; Jiang, Dongneng; Zhou, Linyan; Wang, Deshou
Abstract: Studies of gene function in non-model animals have been limited by the approaches available for eliminating gene function. The CRISPR/Cas9 (c lustered r egularly i nterspaced s hort p alindromic r epeats/C RISPR as sociated) system has recently become a powerful tool for targeted genome editing. Here, we report the use of the CRISPR/Cas9 system to disrupt selected genes, including nanos2, nanos3, dmrt1, and foxl2, with efficiencies as high as 95%. In addition, mutations in dmrt1 and foxl2 induced by CRISPR/Cas9 were efficiently transmitted through the germline to F1 . Obvious phenotypes were observed in the G0 generation after mutation of germ cell or somatic cell-specific genes. For example, loss of Nanos2 and Nanos3 in XY and XX fish resulted in germ cell-deficient gonads as demonstrated by GFP labeling and Vasa staining, respectively, while masculinization of somatic cells in both XY and XX gonads was demonstrated by Dmrt1 and Cyp11b2 immunohistochemistry and by up-regulation of serum androgen levels. Our data demonstrate that targeted, heritable gene editing can be achieved in tilapia, providing a convenient and effective approach for generating loss-of-function mutants. Furthermore, our study shows the utility of the CRISPR/Cas9 system for genetic engineering in non-model species like tilapia and potentially in many other teleost species.